The crisis in Kashmir : portents of war, hopes of peace - Ganguly, Sumit (Cambridge ; New York : Woodrow Wilson Center Press ; Cambridge University Press, 1997)
This book traces the origins, and provides the most complete account, of the insurgency that has racked the Indian-controlled portion (about two-thirds) of Jammu and Kashmir since 1989. The first theoretically grounded account, it is based on extensive interviews with government officials, Kashmiri activists, journalists, members of nongovernmental organizations, and military personnel in India, Pakistan, and the United States.
Ganguly's central argument is that the insurgency can be explained by the linked processes of political mobilization and institutional decay. In an attempt to woo the citizens of India's only Muslim-majority state, the national government in New Delhi dramatically helped expand literacy, mass media, and higher education in Jammu and Kashmir. These processes produced a generation of politically knowledgeable and sophisticated Kashmiris.
Simultaneously, the national government, fearful of potential secessionist proclivities among the Kashmiris, systematically stultified the development of political institutions in the state. Unable to express dissent in an institutional context, this new generation of Kashmiris resorted to violence.
Includes bibliographical references and index.
Keywords: Jammu and Kashmir (India) -- Politics and government